2016
DOI: 10.1038/nm.4052
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class I molecules protect motor neurons from astrocyte-induced toxicity in amyotrophic lateral sclerosis

Abstract: Astrocytes isolated from individuals with amyotrophic lateral sclerosis (ALS) are toxic towards motor neurons (MNs) and play a non-cell autonomous role in disease pathogenesis. The mechanisms underlying the susceptibility of motor neurons to cell death remains unclear. Here, we report that astrocytes derived from mice bearing ALS mutations and from individuals with ALS reduce expression of major histocompatibility complex class I (MHCI) on MNs. Reduced MHCI expression makes these MNs susceptible to astrocyte-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 71 publications
7
99
1
Order By: Relevance
“…Interestingly, they also proved that the OCs of HLA-F and MHC-I are ligands of KIR. Furthermore, research has shown that the OC of HLA-F may be associated with certain diseases, suggesting that a greater understanding of the OCs of HLA-I molecules is needed (44). Consistent with previous results, our data showed that HLA-A11svE4 alone, or in combination with HLA-I OCs, recognizes and combines with KIR to inhibit NK activity, and participates in the Ag-presentation pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, they also proved that the OCs of HLA-F and MHC-I are ligands of KIR. Furthermore, research has shown that the OC of HLA-F may be associated with certain diseases, suggesting that a greater understanding of the OCs of HLA-I molecules is needed (44). Consistent with previous results, our data showed that HLA-A11svE4 alone, or in combination with HLA-I OCs, recognizes and combines with KIR to inhibit NK activity, and participates in the Ag-presentation pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to astrocytes (15,19,(32)(33)(34), however, we report that oligodendrocytes affect MNs through two distinct mechanisms of action: soluble factors and cell-to-cell contact, with the latter being more aggressive. Addition of lactate to the cocultures, in fact, does not rescue MNs.…”
Section: Discussionmentioning
confidence: 72%
“…The molecules encoded by the major histocompatibility complex (MHC) regions regulate the innate and adaptive arms of human immune response through antigen presentation, inflammation regulation and the complement system and the impact of this region in various immune-mediated conditions, including neurological diseases, has long been recognized. [4][5][6][7][8][9] The human MHC gene family maps to chromosome 6. With a size of nearly 5 Mbp it encodes approximately 165 protein-coding genes, many of them immune-related, 10 and comprises approximately 0Á13% of the human genome.…”
Section: The Human Major Histocompatibility Complex Region and Neurolmentioning
confidence: 99%
“…119 Overexpression of HLA-F mediated protection of human motor neurons from ALS astrocyte mediated toxicity. 7 Human metabolites binds with P4 pockets of MS susceptible DRB1*15:01 haplotype in most populations. 233 Fine mapping of the HLA locus suggest DRB1*15 haplotype as a factor for AD.…”
Section: Hla and Multiple Sclerosismentioning
confidence: 99%